Straf for frivillige seksuelle forhold – en arv fra Reformationen? - Kjær, Morten (Nordisk Tidsskrift for Kriminalvidenskab, 2017)
In a newer debate on the criminalization of incest in Denmark, Vagn Greve has argued that the criminalization of consensual sexual relations between adults can be contributed to the German reformer Martin Luther. This article has investigated the impact of the reformation on the sexual offenses with emphasis on their definition and punishment and the question of jurisdiction. The criminalization of consensual sex was not a new phenomenon after the Reformation. Before the Reformation the sexual offences were primarily dealt with by the Catholic Church through its system of penance and its judicial system. After the Reformation the jurisdiction was transferred to the secular authority. For the sexual offences the period 1536-1683 must be viewed as a process. During this period they were incorporated into the secular criminal law culminating with the promulgation of Danske Lov 1683. The following period has to a large extent lead to the decriminalization of the sexual offences. In conclusion, the criminalization of the sexual offences cannot be contributed to the Reformation. It is, however, a legacy of the Reformation that the state assumed the responsibility to punish the sexual offences.